2012
DOI: 10.4314/sajas.v42i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Broiler breeders utilise body lipid as an energy source

Abstract: ________________________________________________________________________________ AbstractThe study was conducted to determine the extent to which broiler breeder hens could make use of excess body lipid reserves as a means of maintaining laying performance. The experiment was divided into two phases. In the first phase, the birds aged 37 weeks were allocated one of four daily allowances: 160, 175, 190 or 205 g of a commercial broiler breeder feed for a period of four weeks in order to achieve four levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this study, the maintenance was expressed in protein unit, as it corrected for growing animals, because it accounts for the maturity degree of protein ( u ), which is the relation of protein weight at a specific age by the mature protein weight. Furthermore, AA are not required for lipid reserves and considering that the amount of lipid might change among individuals [24] it is reasonable to choose body protein as a scale for maintenance calculation.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the maintenance was expressed in protein unit, as it corrected for growing animals, because it accounts for the maturity degree of protein ( u ), which is the relation of protein weight at a specific age by the mature protein weight. Furthermore, AA are not required for lipid reserves and considering that the amount of lipid might change among individuals [24] it is reasonable to choose body protein as a scale for maintenance calculation.…”
Section: Resultsmentioning
confidence: 99%
“…After the cited ages, the laying hens mobilize body fat, possible to maintain egg production, especially after 82 w-old, when the dietary metabolizable energy was reduced, as recommended by the guideline. Nonis and Gous [ 43 ] demonstrated that broiler breeders produce energy from body lipid if they are allowed to do it so, even though the concentration of dietary energy is above requirement, by regulating their feed intake. Similarly, Caldas et al [ 44 ] observed a reduction in broiler breeders fat at the end of egg production phase.…”
Section: Discussionmentioning
confidence: 99%
“…also observed a decrease in fat mass after peak production. Two potential mechanisms might be involved in the decrease in fat mass; 1) body fat is mobilized to support yolk fat or egg (Nonis and Gous, 2012) production or 2) body fat is mobilized to fulfill energy requirements for basic daily protein retention as breeders have not reached their somatically mature weight yet . Breeders fed the 96% AME n diet required a relative high feed intake to achieve pairgaining , where the surplus of nutrients were deposited as fat.…”
Section: Discussion Dynamics In Body Compositionmentioning
confidence: 99%